Value stream analysis of manufacturing engineering new product introduction processes - Maginness, Malachy; Shehab, Essam; Beadle, Chris (Cranfield University, 2011)
This paper describes the use of a methodology for value stream mapping and analysis of Manufacturing Engineering New Product Introduction processes. The applicability and usefulness of the technique to process improvement in this domain is explored in a case study where the production system for a new component part is planned and proven. This analysis enables an improvement strategy for the Manufacturing Engineering process to be successfully outlined.
Keywords: New Product Introduction, Manufacturing Engineering, Aerospace, Lean